2022
DOI: 10.1111/and.14601
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between mean platelet volume and response to treatment with daily tadalafil in patients with erectile dysfunction?

Abstract: Mean platelet volume (MPV) has been related to erectile dysfunction (ED). However, its value in predicting therapeutic response to phosphodiesterase‐5 inhibitors is not evaluated. This study aimed to investigate the value of MPV as a marker for the prediction of the response of the tadalafil treatment of ED. A retrospective analysis of patients who were admitted to the andrology outpatient clinic between 2020–2022 were performed. The inclusion criteria were, ≥40 years old male, International Index of Erectile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Tadalafil, a phosphodiesterase-5 (PDE-5) inhibitor, is often the preferred oral treatment for ED. Ischemia-perfusion studies have revealed that PDE5 inhibitors prevent endothelial damage [8] Although tadalafil is a safe and effective drug, there are numerous factors that influence its efficacy [9,10]. In this study, we aimed to evaluate the effect of the TyG index on treatment response in patients using tadalafil for ED treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Tadalafil, a phosphodiesterase-5 (PDE-5) inhibitor, is often the preferred oral treatment for ED. Ischemia-perfusion studies have revealed that PDE5 inhibitors prevent endothelial damage [8] Although tadalafil is a safe and effective drug, there are numerous factors that influence its efficacy [9,10]. In this study, we aimed to evaluate the effect of the TyG index on treatment response in patients using tadalafil for ED treatment.…”
Section: Introductionmentioning
confidence: 99%